2014
DOI: 10.9734/bmrj/2014/10572
|View full text |Cite
|
Sign up to set email alerts
|

Clindamycin Resistance among Staphylococcus Aureus Isolated at Mbarara Regional Referral Hospital, in South Western Uganda

Abstract: AimsThe study was conducted to determine the prevalence of Clindamycin (CL) resistance and antimicrobial susceptibility among clinical isolates of Staphylococcus aureus (S. aureus) from Mbarara Regional Referral Hospital (MRRH) in Southwestern Uganda.Study DesignLaboratory based cross sectional study.Place and Duration of the StudyThe study was conducted at the Microbiology department of Mbarara Regional referral hospital between November 2012 and December 2013.MethodologyIn our study, we recruited 300 S. aure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
0
12
2
Order By: Relevance
“…In a multivariate analysis, inducible CLI resistance and cancer were identified as independent predictors of MRSA‐SSI . In a similar study, out of 300 clinical S. aureus isolates, 22 were resistant to VAN, 187 were SXT‐resistant, and 143 were resistant to ERY …”
Section: Resultsmentioning
confidence: 88%
“…In a multivariate analysis, inducible CLI resistance and cancer were identified as independent predictors of MRSA‐SSI . In a similar study, out of 300 clinical S. aureus isolates, 22 were resistant to VAN, 187 were SXT‐resistant, and 143 were resistant to ERY …”
Section: Resultsmentioning
confidence: 88%
“…Of the 34 full-text articles available, 22 were excluded, because the data presented were from non-East African countries that were inseparable from data presented about East African countries ( n = 5) or their laboratory methods were not well defined ( n = 17) ( Figure 1 ). The remaining 12 articles were included in this review, six describing AMR patterns in Uganda, 10 , 11 , 12 , 13 , 14 , 15 five in Ethiopia 16 , 17 , 18 , 19 , 20 and one in Tanzania 21 ( Table 1 ). Neither studies from Rwanda nor studies from the Democratic Republic of the Congo met inclusion criteria for this review.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, S. aureus also showed significant resistance to trimethoprim-sulfamethoxazole (62%) and oxacilin (36%), with a demonstrated prevalence of MRSA equal to 36%. 12 Resistance to vancomycin, one of the last-line drugs for treating MRSA, was also found (7.3%). 12 …”
Section: Resultsmentioning
confidence: 99%
“…Among the MRSA strains identi ed, 45.5% (23/50) and 2% (1/50) phenotypically co-expressed inducible clindamycin resistance (MLS B resistance marker) and vancomycin resistance respectively. A study by Mwanbi et al conducted in Uganda on clinical isolates reported a closely similar prevalence rate (36%) of clindamycin resistance (33). Resistance to clindamycin would have been due to an increased use of the drug for patient management in the region.…”
Section: Mrsa Carriage Prevalence and Associated Carriage Risk Factorsmentioning
confidence: 87%